2004
DOI: 10.1128/aem.70.7.4249-4255.2004
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Synthesis of High-Molecular-Mass Poly-γ-Glutamate and Regulation of Its Stereochemistry

Abstract: For the first time, we succeeded in synthesizing in vitro poly-␥-glutamate (PGA) with high molecular masses (>1,000 kDa) by the use of enzyme-associated cell membranes from Bacillus subtilis subsp. chungkookjang. The activity for PGA synthesis, however, was readily lost in the presence of critical concentrations of detergents tested in micelles. The optimum pH for the reaction was found to be ϳ7.0. We examined the effects of some divalent cations on PGA synthesis and found that Mg 2؉ was essential in catalysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 35 publications
4
58
0
Order By: Relevance
“…The latter can indeed accept c-glutamyl compounds with the Dconfiguration as donors, but amino acid acceptors have to be in the L-configuration [3,13]. The similar results obtained when L-glutamine and D-glutamine were subjected to the action of B. subtilis c-GT could, once again, be related to the involvement of the enzyme in homeostasis of the extracellular poly-c-glutamic acid, as this polymeric material is usually formed by L-glutamic acid and D-glutamic acid units [50] in different proportions, depending on the Bacillus strain and environmental conditions [51,52].…”
Section: Ph-dependent Behavior Of B Subtilis C-gt Towards Glutaminesupporting
confidence: 60%
“…The latter can indeed accept c-glutamyl compounds with the Dconfiguration as donors, but amino acid acceptors have to be in the L-configuration [3,13]. The similar results obtained when L-glutamine and D-glutamine were subjected to the action of B. subtilis c-GT could, once again, be related to the involvement of the enzyme in homeostasis of the extracellular poly-c-glutamic acid, as this polymeric material is usually formed by L-glutamic acid and D-glutamic acid units [50] in different proportions, depending on the Bacillus strain and environmental conditions [51,52].…”
Section: Ph-dependent Behavior Of B Subtilis C-gt Towards Glutaminesupporting
confidence: 60%
“…PgsB and PgsC together form most parts of the complex's catalytic site, whereas PgsA seems to remove the elongated chain from the active site so that the next monomer can be added and may also be involved in transporting c-PGA (Ashiuchi et al, 2001b;Urushibata et al, 2002a). Activity of PgsBCA was found to be dependent on Mg 2+ (Ashiuchi et al, 2004). Transportation of c-PGA outside the cell could be facilitated by a less compact cell membrane with shorter phospholipids (Buescher & Margaritis, 2007).…”
Section: C-pga Polymerizationmentioning
confidence: 94%
“…Research has, however, shown that Mn 2+ affects the enantiomeric composition of c-PGA (Cromwick & Gross, 1995a, b;Pérez-Camero et al, 1999;Wu et al, 2006). Ashiuchi et al (2004) showed that Mn 2+ affected the enantiomeric composition by altering the expression of the glr gene. The ratio between L-and D-glutamate in Bacillus licheniformis c-PGA also depends on the concentration of Co 2+ and Zn 2+ .…”
Section: Mechanism Of Synthesis Of C-pgamentioning
confidence: 99%
“…Although two distinct mechanisms for the biosynthesis of DL-PGA have been proposed, 1) it was difficult to assess whether, in the polymer production by B. subtilis cells, it is formed from L-glutamate alone, 4,5) as does B. licheniformis, or whether D-glutamate also serves as a substrate 6) according to an amide ligase 7,8) -like manner. 9,10) Intricate regulation of PGA production in B. subtilis 11,12) causes a difficulty in the interpretation of this issue. In this study, to simplify the regulation of PGA production and construct a more convenient PGA producer, genetic alterations were preformed to B. subtilis ISW1214, which is a tetracycline-susceptible derivative from the 1012 strain of B. subtilis R 13,14) and also the leucine/methionine auxotroph.…”
mentioning
confidence: 99%